Audit of oxygen use in emergency ambulances and in a hospital emergency department. Issue 11 (27th October 2008) - Hale, K E; Gavin, C; O'Driscoll, B R
Abstract : Background: Oxygen is widely used but poorly studied in emergency medicine, with a limited evidence base for its use in specific conditions. There are safety concerns about the underuse of oxygen in patients with critical illness and its overuse in conditions such as chronic obstructive pulmonary disease (COPD). A baseline audit was required to assess current practice prior to the introduction of new national emergency oxygen guidelines in late 2008. Methods: The use of pulse oximetry and oxygen therapy was audited in patients brought by ambulance to the "majors" section of the emergency department (ED) in a university hospital. Oxygen therapy in the ambulance and the ED was subsequently documented. Oxygen use in ambulances was compared with Joint Royal Colleges Ambulance Liaison Committee (JRCALC) guidance and with subsequent patient management. Results: The ambulance and ED records of 1022 patients were audited manually. Oxygen saturation (Spo 2 ) was recorded for 90% of patients, 17% of whom had Spo 2 <94% at some time and 7% had Spo 2 <90%, including 33% of patients with COPD and 5.5% of patients without COPD. 34% of patients received oxygen in the ambulance and almost half of these had oxygen discontinued in the ED. Only 62% of ambulance oxygen use was in accordance with JRCALC guidance, but most "undertreated" patients were stable normoxaemic patients for whom guidance recommends high-flow oxygen. Only 58% of patients with COPD were correctly identified in the ambulance and 73% of these patients were treated with flow rates >4 l/min (equivalent to >35% oxygen). Conclusions: Oxygen use in ambulances is very common, equivalent to 2.2 million episodes annually in the UK. The quality of oxygen use is suboptimal, especially for patients with COPD. Emergency oxygen therapy will become simpler when new evidence-based UK emergency oxygen guidelines are published, and it is hoped that future audits will show better protocol adherence.